2012
DOI: 10.1007/s11033-012-2147-1
|View full text |Cite
|
Sign up to set email alerts
|

Expression pattern of fifteen genes of non-mevalonate (MEP) and mevalonate (MVA) pathways in different tissues of endangered medicinal herb Picrorhiza kurroa with respect to picrosides content

Abstract: Picrorhiza kurroa, has become an endangered medicinal herb due to excessive utilization, therefore it necessitates the understanding of biology and molecular basis of major chemical constituents i.e. Picroside-I (P-I) and Picroside-II (P-II). Estimation of P-I and P-II in different tissues of P. kurroa showed that shoots contain only P-I whereas P-II is present only in roots. Differential conditions with varying concentrations of P-I (0-27 μg/mg) and P-II (0-4 μg/mg) were selected. Four genes of MEP pathway; D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 39 publications
0
34
0
Order By: Relevance
“…Previous studies have shown that shoots grown in tissue culture at 25°C (PKS-25) contain negligible P-I, whereas shoots grown in tissue culture at 15°C (PKS-15) contain slight P-I content (6 lg/mg) (Sood and Chauhan 2010). On the other hand, field-grown shoots (PKSS) contain a considerable amount of P-I content (27 lg/mg) (Pandit et al 2013), which is a contrasting condition for analyzing picroside biosynthesis at molecular level. Spatio-temporal biosynthesis and accumulation of secondary metabolites is influenced by conditions of organ, tissue specificity, and developmental stages of the plant as reported in case of cell type-specific localization of protoberberine alkaloid in roots and rhizomes of T. flavum (Samanani et al 2005) and in Fagopyrum species (Gupta et al 2011).…”
Section: Expression Analysis By Qrt-pcrmentioning
confidence: 99%
“…Previous studies have shown that shoots grown in tissue culture at 25°C (PKS-25) contain negligible P-I, whereas shoots grown in tissue culture at 15°C (PKS-15) contain slight P-I content (6 lg/mg) (Sood and Chauhan 2010). On the other hand, field-grown shoots (PKSS) contain a considerable amount of P-I content (27 lg/mg) (Pandit et al 2013), which is a contrasting condition for analyzing picroside biosynthesis at molecular level. Spatio-temporal biosynthesis and accumulation of secondary metabolites is influenced by conditions of organ, tissue specificity, and developmental stages of the plant as reported in case of cell type-specific localization of protoberberine alkaloid in roots and rhizomes of T. flavum (Samanani et al 2005) and in Fagopyrum species (Gupta et al 2011).…”
Section: Expression Analysis By Qrt-pcrmentioning
confidence: 99%
“…MEP pathway was discovered in 1990s (Rohmer et al 1993), that starts from the condensation of glyceraldehyde-3-phosphate and pyruvate to produce DXP as the first intermediate. The key evidence for the involvement of MVA and MEP pathways in biosynthesis of picrosides was provided by the gene expression analyses performed under differential conditions of picrosides accumulation in P. kurroa (Pandit et al 2013b). Moreover, the gene expression patterns vis-à-vis P-I content were also observed in P. kurroa shoots at different time intervals of plant growth at 15°C under tissue culture conditions.…”
Section: Biosynthesis Of Iridoid Glycosidesmentioning
confidence: 95%
“…The selected genes encoded the enzymes of glycolysis (hexokinase, HK; pyruvate kinase, PK), TCA cycle (isocitrate dehydrogenase, ICDH; malate dehydrogenase, MDH), pentose phosphate pathway (glucose-6-phosphate dehydrogenase, G-6-PDH), shikimate/phenylpropanoid pathway (3-deoxy-D-arabinoheptulosonate 7-phosphate synthase, DAHPS; phenylalanine ammonia lyase, PAL), mevalonate pathway (hydroxymethylglutaryl-CoA reductase, HMGR) and nonmevalonate pathway (1-deoxy-D-xylulose-5-phosphate synthase, DXPS). In addition, the genes encoding the enzymes, 4-diphosphocytidyl-2C-methyl-D-erythritol synthase (ISPD) and phosphomevalonate kinase (PMK) were also selected which previously showed enhanced elevation vis-à-vis P-I content under different growth conditions of P. kurroa (Pandit et al 2013b). The gene coding geraniol synthase (GS) was also selected as it showed significant fold increase in shoots of P. kurroa exposed to 15°C as compared to 25°C (Gahlan et al 2012).…”
Section: Selection Of Genesmentioning
confidence: 99%
“…Finally, geraniol-10-hydroxylase (G-10-H) gene was chosen as it is one of the first two genes in P-I biosynthesis which was used as a bait to decipher the enzymes of seco-iridoid pathway in Catharanthus roseus (Miettinen et al 2014). The primers of mevalonate and non-mevalonate pathway genes (DXPS, ISPD, HMGR and PMK) were procured from Pandit et al (2013b) while glycolysis (HK, PK), TCA cycle (ICDH, MDH) and pentose phosphate pathway (G6PDH) were procured from Kumar et al (2015). The primers for rest of the selected genes were designed from transcriptomic sequences of P. kurroa by using Primer3 software.…”
Section: Selection Of Genesmentioning
confidence: 99%
See 1 more Smart Citation